Belajar Kosa Kata Bahasa Inggris Melalui Lagu Dengan Aktivitas Stereophonic Styrofoam: SD IT Nurul Fikri Palangka Raya - Abdul Syahid; Aulia Rahmi; Devi Hanas Tasya; Krisna Dwi Alifhia Rezky; Mirna Lestari; Meisya Rawenda; Nuralisa Nuralisa; Umi Maisarah; Wafa’ Qaulan Syahida (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The initiative